Relationship of PM2.5 Value between Rain-No Rain & Indoor-Outdoor on Occupational Health and Safety Information System Development (Study Case in East Bekasi, West Java - Indonesia) - Tika Endah Lestari; Wandy Wandy (Universitas Muhammadiyah Purworejo, 2022)
Air quality is vital to be measured for indoor and outdoor situations, and this air quality relates directly to humans. Occupational Health and Safety is the efficient operation of a task that significantly influences the level of safety and comfort of a working environment. It is a health condition that aims to make the working environment obtain the highest physical, spiritual, and social health to prevent and treat diseases or health problems. This research aimed to analyze whether the PM2.5 data grabbed by the sensor in several situations, when recorded to the database, are valid to be displayed in an appropriate chart and data type when the data is shown on the dashboard. The Rain situation can reduce the PM2.5 value both Indoor and Outdoor, and in East Bekasi, Indoor PM2.5 has a lower value than Outdoor. An expert system or decision support system can be implemented for future dashboard development to show an intelligent dashboard for these Rain-No Rain and Indoor-Outdoor situations. The data from the sensor may show as an Integer data type without the decimal, but during the analysis, the data required decimal values for average, standard deviation, and PM2.5 trends. A gauge chart will be appropriate for real-time data, and a bar/line chart will be good for historical data.